2020
DOI: 10.1088/1674-1056/ab84cf
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical design of single-molecule NOR and XNOR logic gates by using transition metal dibenzotetraaza[14]annulenes*

Abstract: The idea of replacing traditional silicon-based electronic components with the ones assembled by organic molecules to further scale down the electric circuits has been attracting extensive research focuses. Among the molecularly assembled components, the design of molecular logic gates with simple structure and high Boolean computing speed remains a great challenge. Here, by using the state-of-the-art nonequilibrium Green’s function theory in conjugation with first-principles method, the spin transport propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Since the experiment shows that the current-voltage characteristics have been measured as being stable at room temperature, [37] the optimized structures in our calculations should also reach a stable state at room temperature. [48][49][50][51][52][53] Furthermore, another two interesting effects ca also be observed from these I-V curves: (i) Rectifying effect. The rectification ratio is defined as RR = I(−V )/I(V ), where I(−V ) and I(V ) correspond to the currents under negative and positive biases with the same voltage magnitude.…”
Section: Methods and Modelmentioning
confidence: 76%
“…Since the experiment shows that the current-voltage characteristics have been measured as being stable at room temperature, [37] the optimized structures in our calculations should also reach a stable state at room temperature. [48][49][50][51][52][53] Furthermore, another two interesting effects ca also be observed from these I-V curves: (i) Rectifying effect. The rectification ratio is defined as RR = I(−V )/I(V ), where I(−V ) and I(V ) correspond to the currents under negative and positive biases with the same voltage magnitude.…”
Section: Methods and Modelmentioning
confidence: 76%
“…22 Besides, researchers have theoretically studied the spin transport properties of several transition metal dibenzotetraaza[14]annulenes sandwiched between nonmagnetic gold, graphene or carbon nanotube electrodes, and found that perfect spin filtering can be obtained when Fe- and Co(DBTAA) molecules are used. 23–25 In this study, by employing magnetic Fe electrodes and the magnetic Mn(DBTAA) molecule, we focus on exploring the influence of interface structures on magnetic and electronic couplings between the Fe electrode and the Mn(DBTAA) molecule, and the subsequent spin transport behaviours. The results reveal that the interface structures can modulate and even reverse the spin polarization of tunneling electrons over a wide range.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the design and manufacturing of spin molecular devices being able to perform specific logical functions has attracted ever-increasing attention owing to the rapid development of molecular spintronics. [1][2][3][4] In these socalled spin molecular logic gates, magnetic molecular materials can switch among different states under the action of one or more input signals, and such transition leads to a single logical output signal. Evidently, selection of appropriate magnetic molecular materials becomes a key fac-tor to construct spin molecular logic gates.…”
Section: Introductionmentioning
confidence: 99%